Фантастика Станислава Гагарина - Гагарин Станислав Семенович (Библиотека "Русские приключения", 1995)
Экземпляры: ФО-3 (20250225) / Инвентарный номер: 30433z3 / Цена: / Сис.шифр: 84(2Pос=Рус)6 / Авт.знак: Г 12 / ГРНТИ: 17.82.31 / ББК: 84(2Pос=Рус)6